Impact of zirconia-based oxide on endothelial cell dynamics and extracellular matrix remodeling - de Almeida Camargo, Beatriz [UNESP]; da Silva Feltran, Geórgia [UNESP]; Fernandes, Célio Junior da Costa [UNESP]; Carra, Maria Gabriela [UNESP]; Saeki, Margarida Juri [UNESP]; Zambuzzi, Willian F. [UNESP] (Elsevier, 2024)
Introduction: Zirconia (ZrO2) is highly regarded in dental restoration due to its aesthetic compatibility and mechanical properties that align with biological tissues. This study explores the effects of stabilized ZrO2 on endothelial cell function and extracellular matrix (ECM) remodeling, processes critical to successful osseointegration in dental implants. Methodology: Human Umbilical Vein Endothelial Cells (HUVECs) were cultured in ZrO2 -enriched medium under both static and shear stress conditions. Newly implemented techniques, including detailed zirconia surface characterization using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD), were used to verify material properties. Gene and protein expression related to cell adhesion, proliferation, and ECM remodeling were assessed through RT-qPCR and Western blotting. Zymography was used to evaluate the activity of matrix metalloproteinases (MMP2 and MMP9) involved in ECM remodeling. Results: Characterization data confirmed the stability and structural properties of ZrO2, revealing a tetragonal crystalline structure and rough surface morphology conducive to cell adhesion. ZrO2 exposure led to the downregulation of Src, a key regulator of cell adhesion, while upregulating cell cycle regulators p15, CDK2, and CDK4, indicating enhanced cell proliferation. Under shear stress, ZrO2 modulated TGF-β and MAPK signaling, affecting cell proliferation and angiogenesis. MMP2 and MMP9 activity increased in static conditions but decreased under shear stress, suggesting ZrO2 dynamic role in ECM remodeling. Conclusion: This study shows that stabilized zirconia (ZrO2) modulates endothelial cell dynamics and ECM remodeling, key for osseointegration. ZrO2 downregulated Src expression and upregulated cell cycle regulators, enhancing endothelial proliferation. It also affected TGF-β and MAPK pathways, influencing angiogenesis, and differentially modulated MMP2 and MMP9 activity depending on mechanical conditions. These findings highlight ZrO2 has potential ability to enhance vascular and tissue integration in dental applications.
Keywords: Cell Cycle Regulation; Endothelial Cells; Extracellular Matrix Remodeling; Shear Stress; Stabilized Zirconia